Optimization design and test of rice plug seedling transplanting mechanism of planetary gear train with incomplete eccentric circular gear and non-circular gears - Bingliang, Ye; Weiming, Yi; Gaohong, Yu; Yang, Gao; Xiong, Zhao (International Journal of Agricultural and Biological Engineering, 2017)
In order to solve the problem of the high-speed mechanized transplanting of rice plug seedlings, the design requirements of transplanting mechanism for rice plug seedlings were analyzed and a kind of rice plug seedling transplanting mechanism of planetary gear train based on the drive with incomplete eccentric circular gear and non-circular gears was designed innovatively. The laboratory kinematics was examined. The working principle of the transplanting mechanism for rice plug seedlings was studied, kinematics analysis of the transplanting mechanism was carried out and its kinematic model was set up. A human-computer interaction optimization method was used to optimize the parameters of the transplanting mechanism. The computer aided analysis and optimization software of the transplanting mechanism based on Visual Basic 6.0 was developed. Through analyzing the influence of design variables on the optimization objectives of the transplanting mechanism, a set of parameters of the transplanting mechanism which meet the requirements of transplanting trajectory and posture for transplanting rice seedlings were obtained by means of human-computer interaction. The structure of the transplanting mechanism was designed according to this set of parameters, and its virtual prototype and physical prototype were set up and manufactured, respectively. The kinematic simulation test and high-speed photography kinematic test of the transplanting mechanism were conducted to obtain its kinematic performances, such as transplanting trajectory and posture. The results of bench test, simulation analysis and theoretical analysis were almost in agreement, which verified the correctness of the theoretical model and design results of the transplanting mechanism, indicating that the optimized transplanting mechanism can satisfy the requirements of transplanting rice seedlings and be applied in the rice plug seedling transplanter.Keywords: plug seedling, transplanting mechanism, incomplete eccentric circular gear, non-circular gear, planetary gear train, optimization designDOI: 10.25165/j.ijabe.20171006.2712Citation: Ye B L, Yi W M, Yu G H, Gao Y, Zhao X. Optimization design and test of rice plug seedling transplanting mechanism of planetary gear train with incomplete eccentric circular gear and non-circular gears. Int J Agric & Biol Eng, 2017; 10(6): 43–55.